Utility of Tolonium Chloride Rinse in the Diagnosis of Oral Cancer (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Oral cancer burden in developing countries is huge. In Bangladesh and India incidence were 10.6% and 10.4% respectively on 2018. At the same time worldwide incident was only 2%. Majority patients present at advanced stage and their survival rate is poor. Diagnostic delay from patient side and health delivery system side is significantly longer and it is more in developing countries. Like other malignancy early diagnosis can save a lot of these patient.Methods: This prospective study was carried out in Khulna Medical College Hospital from July 2017 to July 2019. Patients who will meet the criteria for this prospective study and capable and willing to give informed consent were enrolled. 20 second rinse/gargle with 10ml of 1% Tolonium chloride solution was done. Biopsy were taken from stained lesion, biopsy report were compared with TC stained lesions.Results: Out of 1650 patients in our outdoor department for various problem and only 30 cases were selected for this study according to selection criteria. Of 30 patients, 18 (60%) were male and 12 (40%) were female. The male-to-female ratio was 3:2. It was found that the sensitivity of 1% Tolonium Chloride rinse for oral precancer and cancer detection was 83.33%, whereas the specificity was 84.21%.Conclusion: Tolonium chloride rinse is a good screening test for oral cancer diagnosis with sensitivity 83.33% and specificity 84.21%.Bangladesh J Otorhinolaryngol; April 2020; 26(1): 11-17